Efforts to Cultivate Habituation-Based Character Education in Students of Kalibaru State Vocational High School (SMK) Banyuwang - Susiana; M. Ngantori (Edumaspul: Jurnal Pendidikan, 2026)
Character education is the process of instilling positive values in students through various effective methods so that these values can be consciously applied without coercion. Successful character education instillation requires synergy from all school components, both through the school’s flagship program and the active role of teachers in guiding students. This study aims to examine the efforts of Kalibaru State Vocational School (SMK Negeri Kalibaru) in instilling habit-based character education, identify supporting and inhibiting factors, and determine the results of implementing this character education among students. This study used a qualitative approach with a case study, in which the researcher served as the primary instrument, while data collection was conducted through observation and interviews, mostly conducted online. The results indicate that the efforts to instill habit-based character education at Kalibaru State Vocational School (SMK Negeri Kalibaru) have been running according to the school program, although several supporting and inhibiting factors have been identified. Overall, the process of instilling character in students has been successful, with the implementation of rewards and punishments helping teachers instill discipline and accustom students to applying character values, ensuring the school’s program runs smoothly. Abstrak Pendidikan karakter merupakan proses penanaman nilai-nilai positif kepada peserta didik melalui berbagai metode yang efektif sehingga nilai tersebut dapat diterapkan secara sadar tanpa paksaan. Keberhasilan penanaman pendidikan karakter memerlukan sinergi seluruh komponen sekolah, baik melalui program unggulan sekolah maupun peran aktif guru dalam membimbing peserta didik. Penelitian ini bertujuan untuk mengetahui upaya SMK Negeri Kalibaru dalam menanamkan pendidikan karakter berbasis pembiasaan, mengidentifikasi faktor pendukung dan penghambatnya, serta mengetahui hasil dari penerapan pendidikan karakter tersebut pada peserta didik. Penelitian ini menggunakan pendekatan kualitatif dengan jenis studi kasus, di mana peneliti berperan sebagai instrumen utama, sedangkan teknik pengumpulan data dilakukan melalui observasi dan wawancara yang sebagian besar dilaksanakan secara daring. Hasil penelitian menunjukkan bahwa upaya penanaman pendidikan karakter berbasis pembiasaan di SMK Negeri Kalibaru telah berjalan sesuai dengan program sekolah, meskipun terdapat beberapa faktor pendukung dan penghambat dalam pelaksanaannya. Secara umum, proses penanaman karakter pada peserta didik berhasil dengan baik, di mana penerapan reward dan punishment turut membantu guru dalam menanamkan kedisiplinan serta membiasakan peserta didik untuk menerapkan nilai-nilai karakter sehingga program sekolah dapat berjalan sebagaimana mestinya.